Comprehensive impact of Intermittent Hypoxia Training and Intermittent Fasting on metabolic and cognitive health in adults with obesity: an umbrella systematic review and meta-analysis - Guo, Jiajia; Zhang, Ning; Chen, Juan; Liu, Xueyu (Frontiers in Nutrition, 2025)
BackgroundObesity has emerged as a global health crisis, posing significant challenges to metabolic function and cognitive health. It is associated with insulin resistance, elevated triglycerides, and reduced HDL cholesterol levels. Cognitive decline in obesity involves multifactorial pathways including neuroinflammation, vascular dysfunction, and blood–brain barrier disruption. Intermittent Hypoxia Training (IHT) and Intermittent Fasting (IF) have shown promise as non-pharmacological interventions for these obesity-related issues.ObjectivesThis systematic review and meta-analysis aim to evaluate the effects of IHT, IF, and their combination on metabolic markers (insulin sensitivity, lipid profiles, glucose levels) and specific cognitive domains (memory, executive function, attention) and cognitive function in obese adults.MethodsThe analysis encompassed studies published from October 2014 onward, sourced from PubMed, Web of Science, Scopus, and other relevant databases. The inclusion criteria were randomized controlled trials and non-randomized comparative studies focusing on IHT, IF, or their combination. Study quality was assessed using the Newcastle-Ottawa Scale and the Cochrane risk bias tool. Data synthesis was performed using a random-effects model, with heterogeneity assessed via I2 statistics.ResultsThe review included 28 studies involving 2,134 participants, followed up for an average of 12 weeks. Among these, 15 were RCTs and 13 were observational studies. The participants had a mean age of 45 ± 12 years, with 60% being female. The combined IHT and IF intervention demonstrated superior benefits, with significant weight loss (mean reduction: 6.3 kg, 95% CI: −8.2 to −4.5 kg). Cognitive performance showed domain-specific improvements: memory (SMD = 0.60, 95% CI: 0.43–0.77) and attention (SMD = 0.57, 95% CI: 0.40–0.74), though with significant heterogeneity (I2 > 50%). Egger’s test indicated minimal publication bias (p = 0.18).ConclusionOur meta-analysis reveals that IHT and IF may serve as promising non-drug strategies for improving metabolic and cognitive outcomes in adults with obesity. Given the short-term evidence and methodological heterogeneity, long-term studies are needed to confirm these findings.